2006
DOI: 10.1007/s00415-006-0217-9
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of current utilisation of complementary and alternative medicine by patients with multiple sclerosis

Abstract: Since MS patients are frequently using CAM despite the absence of clinically proven efficacy and appraise it positively, further research on the motivation for utilisation and on objective effects of CAM are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
54
3
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 30 publications
13
54
3
3
Order By: Relevance
“…In addition, a study in Germany found that the majority of complementary and alternative therapies use by people with multiple sclerosis happens in the early stages of the disease as initially they explore all avenues (Kochs et al, 2014). As the participants in this sample had a mean time since diagnosis of 16 years this may explain why complementary and alternative therapies use was lower that most of previous research where, when reported, time since diagnosis was from seven to nine years (Apel et al, 2006;Gedizlioglu et al, 2015).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In addition, a study in Germany found that the majority of complementary and alternative therapies use by people with multiple sclerosis happens in the early stages of the disease as initially they explore all avenues (Kochs et al, 2014). As the participants in this sample had a mean time since diagnosis of 16 years this may explain why complementary and alternative therapies use was lower that most of previous research where, when reported, time since diagnosis was from seven to nine years (Apel et al, 2006;Gedizlioglu et al, 2015).…”
Section: Discussionmentioning
confidence: 67%
“…This result was lower than complementary and alternative therapies use in Germany (67%) (Apel et al, 2006), the United States of America (58%) (Stoll et al, 2012) and the Nordic countries (46-58%) (Skovgaard et al, 2012) but higher than complementary and alternative therapies use in Turkey (26%) (Gedizlioglu et al, 2015). The majority of the participants in the studies which reported higher complementary and alternative therapies usage had relapsing remitting multiple sclerosis and were mildly or moderately affected.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In CAM surveys in developed Western countries, the educational level of CAM users was reported to be higher than that of non-users [17,[24][25][26][27]. However, other studies have reported that the educational level of CAM users was lower than that of non-users [28] or that educational level was not correlated with CAM usage at all [29,30]. Therefore, the influence of education level on CAM and TKM usage is ambiguous and debatable.…”
Section: Discussionmentioning
confidence: 95%
“…Exercise, meditation, yoga, relaxation, acupuncture, cannabis, massage, dietary changes, vitamins, therapeutic herbs or mineral supplements are a few examples of such means and methods. (1,2,3,4,5) There is, however, little evidence for the benefit of these applications (6). As with many other chronic diseases, the use of alternative and complementary treatment (ACT) is getting more widespread for MS and there is a growing accumulation of knowledge about them globally.…”
Section: Introductionmentioning
confidence: 99%